Georges Tarabichi: A contemporary reading of rationality and enlightenment in Islamic civilization - Salman, Wasim (Münster journal for Islamic and philosophical studies, 2022)
This study of rationality and enlightenment in Islamic thought is based on the writings of the Syrian thinker George Tarabishi‭ (‬1939-2016‭) ‬and his defense of freedom of thought‭, ‬philosophy and creativity‭. ‬Tarabishi devoted a quarter of a century of his life to arguing with the writer of Critique of Arab Reason Mohammed Abed al-Jabri‭, ‬who confirmed the contradiction of Arab-Islamic‭ ‬thought with philosophy‭. ‬This paper aims to underline the unity of the Arab-Islamic Reason‭, ‬through tarabishi›s response to al-Jabri›s theory‭, ‬and to emphasize the rational structure of oriental philosophy and its Aristotelian reference‭.‬